2006
DOI: 10.1177/014107680609900315
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Cardiovascular Events and Celecoxib: a Systematic Review and Meta-Analysis

Abstract: The available data indicate an increased risk of myocardial infarction with celecoxib therapy, consistent with a class effect for COX-2 specific inhibitors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(50 citation statements)
references
References 31 publications
2
48
0
Order By: Relevance
“…However, uncertainty remains about the nature of such risks as well as the relative safety of NSAIDs (Bhala et al 2013;Caldwell et al 2006;Chen et al 2008;Henry 2006, 2011;Salvo et al 2011;Trelle et al 2011). Our analysis agrees with the limited number of studies that have looked for, and found, that NSAIDs are not only heterogeneous in their extent of CV/renal risks but also differ in the nature of their adverse effects on different body systems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, uncertainty remains about the nature of such risks as well as the relative safety of NSAIDs (Bhala et al 2013;Caldwell et al 2006;Chen et al 2008;Henry 2006, 2011;Salvo et al 2011;Trelle et al 2011). Our analysis agrees with the limited number of studies that have looked for, and found, that NSAIDs are not only heterogeneous in their extent of CV/renal risks but also differ in the nature of their adverse effects on different body systems.…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that inflammatory conditions, in general, and arthritis, in particular, are associated with increased morbidity and mortality mainly due to CV complications (Jamali 2007). In addition, since emphasis is usually given to the composite CV/renal risk, the nature of the adverse effects of NSAIDs (e.g., myocardial, vascular and renal) have remained mainly unknown (Caldwell et al 2006;Juni et al 2004). A differentiation between these outcomes is essential as not all NSAIDs carry the same potential of influencing a particular system in the body.…”
Section: Introductionmentioning
confidence: 99%
“…A concern that has arisen lately regarding the use of COX-2 inhibitors is the increasing risk of cardiovascular diseases, as shown in a few meta-analysis assessing the risk of MI with selective COX-2 inhibitors including celecoxib [163][164][165][166]. For that reason, cautious use may have to be considered in high risk patients for cardiovascular disease.…”
Section: Celecoxibmentioning
confidence: 99%
“…Cyclooxygenase-2 (COX-2) inhibitor use is associated with adverse side effects, including gastrointestinal complications and increased risk of myocardial infarction [3]. Although effective in the short-term, multiple corticosteroid injections in a joint and prolonged exposure to steroids can harm articular cartilage and accelerate progression of OA [4].…”
Section: Introductionmentioning
confidence: 99%